Effect of Cord Blood Magnesium Level at Birth on Non-neurologic Neonatal Outcomes - Edwards, James M.; Edwards, Laura E.; Swamy, Geeta K.; Grotegut, Chad A. (American Journal of Perinatology, 2019)
Objective We examined the effects of magnesium sulfate on non-neurologic neonatal outcomes with respect to cord blood magnesium level.Study Design We conducted a secondary analysis of the Maternal-Fetal Medicine Units Beneficial Effects of Antenatal Magnesium (MFMU BEAM) trial comparing the upper and lower quintiles of cord blood magnesium level. Outcomes included cerebral palsy (CP), necrotizing enterocolitis (NEC), retinopathy of prematurity (ROP), bronchopulmonary dysplasia (BPD), and assessments of mental and motor disability. Logistic regression was used to estimate adjusted odds ratios (aORs) of each outcome, controlling for gestational age (GA), birth weight, and treatment group (TG).Results A total of 1,254 women of the 2,444 included in the BEAM trial had cord blood magnesium levels recorded. GA and birth weight were lower and TG was more common in the upper quintile cohort (p < 0.001). Neonates in the upper quintile were more likely to have severe NEC (OR, 2.41, 95% confidence interval [CI]: 1.11–5.24), ROP (OR, 1.65, 95% CI: 1.05–2.59), and BPD (OR, 1.70, 95% CI: 1.04–2.73). Adjustment for covariates demonstrated no difference in the NEC, ROP, and BPD rates, although there was a decrease in rates of mental disability index < 70 which was not seen in the unadjusted analysis (aOR, 0.49, 95% CI: 0.25–0.99).Conclusion Higher cord blood magnesium levels do not appear to have adverse non-neurologic effects on the neonate and may demonstrate improvement in neurologic outcomes.
Keywords: magnesium sulfate; necrotizing enterocolitis; bronchopulmonary dysplasia; neuroprotection; pregnancy; preterm birth